Semantic Peculiarities of the Superlative Degree of Adjectives Formed by Particle -գույն - SARKISYAN, ARTASHES (Bulletin of Yerevan University B: Philology, 2021)
The article studies semantic and functional peculiarities of the superlative degree of adjectives formed by particle -գույն [-guyn]. The superlative degree formed by this particle semantically differs from the superlative adjectives formed by the prepositional particle ամենա- [amena-]. The adjectives with the particle -գույն are mostly used with nouns which express abstract or mental, scientific, cultural conceptions. It is also noted that a small number of superlative adjectives can be formed by this particle. The particle ամենա- is more universal.